MANFAAT LIMBAH BATANG JAGUNG DALAM PEMBUATAN PULP - Kusumayanti, Heny; U, Karismawan P; Nila W, Tri Murti (Universitas Diponegoro, 2007)
Absract Existence of paper in human life is important, because paper has function to record science, commerce promotion, medium to extend opinion and idea, and etc. However substance of paper in this time is become thin. For that, we try making pulp from waste of cornâ€™s stem with use soda process and the tool is digester. The colour of product pulp is brown, but after the washing the colour pulp is shine brown because of impurity in the pulp is solute after been washed. The pulp is analyzing more further, between bleaching process, analyses of number permanganate, analyses grade of a cellulose, and grade of ash. The colour of product pulp after bleaching is white brown, grade of Î± cellulose 48.32%, grade of ash 8.8%, number permanganate 8.184. Â Key word : cornâ€™s stem, soda process, bleaching